PENGARUH PEMBERIAN BEBERAPA JENIS BAHAN ORGANIK TERHADAP PENINGKATAN KANDUNGAN HARA N, P, K ULTISOL KEBUN PERCOBAAN FAPERTA UNAND PADANG - Gusmini Gusmini; Yulnafatmawita Yulnafatmawita; Anita Febriani Daulay (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2008)
A research entitled the effect of various sources of organic matter on improvement of N,P,K Nutrient of Ultisol was conducted in Limau Manis Padang. The research was aimed to investigate the contribution of different source of organic matter to improve N,P,K content in soil. Field research was arranged in Randomized Block Design (RBD) consisting 5 treatments and 3 replications (blocks). Treatments are : A = no organic matter added, B = Tithonia, C = Paddy Straw, D = Imperata cylindrica, and E = Leucaena glauca. The dosage for each treatment was 20 ton/ha. The result showed that tithonia gave the best contribution in improving N,P,K content of Ultisol Limau Manis.Keywords :organic matter, N, P, K of Ultisols.